Job Satisfaction of Fitness Professionals in Portugal: A Comparative Study of Gender, Age, Professional Experience, Professional Title, and Educational Qualifications - Ramos, Liliana Ricardo; Esteves, Dulce; Vieira, Isabel; Franco, Susana; Simões, Vera (Frontiers in Psychology, 2021)
This research characterizes and compares the job satisfaction of fitness professionals in Portugal between genders, ages, professional experience, professional title, and educational qualifications. A total of 401 fitness professionals answered the online questionnaire Job Satisfaction Scale which has 16 factors rated on a Likert scale with seven levels. The statistical analysis comprises descriptive and statistical tests to compare the results of two (t-test) or more (ANOVA) groups. Overall, the results demonstrated that fitness professionals were moderately satisfied with their work. The lower degrees of job satisfaction were concerning salary, opportunities for promotion, and stability at work. The highest levels of job satisfaction were related to the freedom to choose their work method, their work colleagues, the physical conditions of their workplace, and the opportunity to use their competencies. There were no differences in job satisfaction in terms of gender, a few differences between professional title and between educational levels. Regarding age and professional experience, the results showed significant differences in almost all factors, suggesting that as fitness professionals get older and more experienced, their job satisfaction is greater. The results of this study suggest that even though fitness professionals are, in general, moderately satisfied with their work, some aspects can be improved by employers to increase their satisfaction levels. Such findings would assist employers in guiding the job satisfaction of their employees with consequent enhancements in the services provided by fitness professionals which can increase participants' retention in exercise fitness activities.